Identification and Characterization of lncRNAs Related to the Muscle Growth and Development of Japanese Flounder (Paralichthys olivaceus) - Wu, Shuxian; Zhang, Jingru; Liu, Binghua; Huang, Yajuan; Li, Siping; Wen, Haishen; Zhang, Meizhao; Li, Jifang; Li, Yun; He, Feng (Frontiers in Genetics, 2020)
LncRNAs play an important role in many life activities, but the expression pattern and function of lncRNAs in the Japanese Flounder skeletal muscles is unclear. In this study, 751 lncRNAs were selected from skeletal muscles in different development stages of Japanese flounder (stage A: larval 7dph, stage B: juvenile about 90dph, stage C (female) and stage D (male): adult about 24 months) by using coding potential analysis methods. In total, 232, 211, 194, 28, 29 and 14 differentially expressed lncRNAs, and 9549, 8673, 9181, 1821, 1080 and 557 differentially expressed mRNAs were identified in comparisons of A vs. B, A vs. C, A vs. D, B vs. C, B vs. D and C vs. D, respectively. Besides, we identified the cis- and trans-regulatory target genes of differentially expressed lncRNAs, and the lncRNA-gene interaction networks was constructed by using Cytoscape program. In total, 200, 200, 200, 93, 47, and 11 cis-regulation relationships, and 29, 19, 24, 38, 8 and 47 trans-regulation relationships were identified in comparisons of A vs. B, A vs. C, A vs. D, B vs. C, B vs. D and C vs. D, respectively. Based on these relationships, functional annotation of related lncRNA was performed by GO and KEGG enrichment analysis. In addition, we predicted lncRNA-mRNA, miRNA-mRNA and lncRNA-miRNA regulatory relationships and constructed interactive network using Cytoscape software. These results provide a basis for further study of the function of lncRNA on skeletal muscle in different development stages of Japanese flounder.